Selective Reporting of Outcomes in Tinnitus Trials: Comparison of Trial Registries With Corresponding Publications - Beurden, Isabeau van; Beek, Megan J. van de; Heteren, Jan A. A. van; Smit, Adriana L.; Stegeman, Inge (Frontiers in Neurology, 2021)
Objectives We aimed to study the prevalence of selective reporting of primary and secondary outcomes in tinni-tus trials and to examine if selective reporting of outcome measures is influenced by the nature and direction of its results. Background Selective reporting of outcome measures has been reported in several biomedical fields and can influ-ence the clinical usefulness and implementation of outcomes of clinical trials. It is reported as one of the obstacles in finding a curen effective intervention for tinnitus. Methods ClinicalTrials.gov (CT.gov) was used to identify all registered interventional tinnitus trials up to Decem-ber 2015. A standardized search was used to find corresponding publications up to March 2018. The prespecified outcomes in CT.gov were compared to the outcomes reported in corresponding publica-tion(s). The effects of the (lack of) statistical significance of trial results and the effects of funding source on record adherence were evaluated. Changes to registration elements were assessed with the Archive site of CT.gov. Results We found corresponding publications for 60 (64.5%) of 93 eligible tinnitus trials registered in CT.gov. Of all the publications, 5 (7.5%) fully reported outcome measures entirely in line with the prespecified outcome measures. Discrepancies between the pre-specified and reported outcomes were found in a total of 51 (76.1%) of the studies for primary outcomes, whereas 62 (92.5%) of the studies had dis-crepancies in secondary outcomes. In secondary outcomes, statistical significance of trial results influ-enced CT.gov record adherence. In addition, there was a statistically significant difference in the rate of discrepancy in industry-funded (n=98 (87.5%) discrepant outcomes) and non-industry funded trials (n=172 (74.5%) discrepant outcomes) (p=0.01). Finally, 15 (25.9%) trialists made modifications in regis-tered outcome measures during or after the trial period. Conclusion Tinnitus trials suffer from substantial outcome reporting bias. Awareness of its presence must be raised to limit the obstacles of finding a curen effective intervention for tinnitus.